Primary adenocarcinoma arising in esophageal colon interposition for corrosive esophageal injury: a case report and review of the literature - De Moura, Diogo Turiani Hourneaux; Ribeiro, Igor Braga; Coronel, Martin; De Moura, Eduardo Turiani Hourneaux; Carvalho, Joana Rita; Baba, Elisa Ryoka; De Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2018)
Background and study aims Colon interposition for benign strictures is associated with significant perioperative complications that carry high morbidity and mortality. Although rarely reported in the literature, adenocarcinoma can occur as a late complication in an interposed colonic segment. We report a case of a late-stage adenocarcinoma in a colonic interposition performed for benign esophageal stricture.